Exploring how papaya juice improves meat tenderness and digestive characteristics in Wenchang chickens - Zihan Zhang; Yucan Wu; Chunhui Zhang; Feng Huang (Poultry Science)
Wenchang chicken meat, used as the primary ingredient, was combined with papaya juice in different proportions for pickling and stewing. The objective of this study was to examine the effects of papain in papaya juice on the tenderness, structure and digestive characteristics of chicken meat. Compared with that in the control group, the tenderness of Wenchang chicken meat decreased and the protein solubility increased with the increase in papaya juice concentration. Scanning electron microscopy (SEM) showed that the arrangement between muscle bundles was from dense to sparse and the surface pores of muscle bundles increased. The results showed that adding papaya juice with a 50% dilution concentration provided the best outcomes in terms of tenderness, structure and digestive characteristics of chicken. Papain in papaya juice interacts with chicken protein, further enhancing the tenderness. The addition of papaya can further improve the tenderness and digestibility of chicken meat.